Effects of Channels and Micropores in Honeycomb Scaffolds on the Reconstruction of Segmental Bone Defects - Shibahara, Keigo; Hayashi, Koichiro; Nakashima, Yasuharu; Ishikawa, Kunio (Frontiers in Bioengineering and Biotechnology, 2022)
Reconstruction of critical-sized segmental bone defects is a key challenge in orthopedics because of its intractability despite technological advancements. To overcome this challenge, scaffolds that can promote rapid bone ingrowth and subsequent replacement with bone are necessary. In this study, we fabricated three types of carbonate apatite honeycomb (HC) scaffolds with uniaxial channels bridging the stumps of a host bone. These HC scaffolds possessed different volumes of channels and micropores in the scaffold struts. The HC scaffolds were implanted into the defects of rabbit ulnar shafts to evaluate the effects of channels and micropores on bone reconstruction. Four weeks postoperatively, the HC scaffolds with higher channel volume promoted bone ingrowth compared to that with higher micropore volume. In contrast, 12 weeks postoperatively, the HC scaffolds with higher volume of micropores rather than channels promoted scaffold resorption by osteoclasts and bone formation. Thus, the channels affected bone ingrowth in the early stage, and micropores affected scaffold resorption and bone formation in the medium term. Furthermore, 12 weeks postoperatively, the HC scaffolds with high volumes of both channels and micropores formed a significantly larger amount of new bone than that attained using HC scaffolds with high volume of either channels or micropores, achieving the bridging of the host bone stumps. The findings provide guidance for designing the pore structure of scaffolds.